Indonesian renewable energy transition and its socio-environmental impacts: Wawonii Island case study - Fadhlillah, Nibras; Karisma, Gita; Rachmawati, Tety (Graduate School of Universitas Brawijaya, 2026)
As global demand for green technologies and renewable energy systems continues to rise, Indonesia has emerged as a strategic actor in the global energy transition due to its vast nickel reserves, estimated at nearly 4 million metric tons. This resource advantage underpins the country’s ambitious nickel downstreaming policy, which is promoted as a cornerstone of green economic transformation and a key driver of the renewable energy transition. However, the implementation of this strategy has generated significant socio-environmental challenges that warrant critical examination. This study analyzes the socio-environmental implications of Indonesia’s nickel downstreaming program, with particular emphasis on its intersection with global green growth narratives. Employing a qualitative descriptive approach, this research adopts a case study of the nickel mining industry on Wawonii Island, Southeast Sulawesi. Data were analyzed to explore how large-scale extractive activities, driven by the global demand for renewable energy components, reshape local socio-ecological systems. The findings reveal a paradox between the global discourse of sustainable energy transition and the realities experienced at the local level. While nickel downstreaming contributes to national economic growth and supports renewable energy supply chains, it simultaneously exacerbates environmental degradation, threatens coastal ecosystems, and undermines the livelihoods and resource access of local communities. This study highlights the hidden socio-environmental costs embedded within the global energy transition and underscores the need for more inclusive, accountable, and sustainable governance frameworks. Strengthening environmental regulation, ensuring community participation, and integrating social justice principles into resource management are essential to achieving a truly sustainable and equitable energy transition.